Design of axially loaded isotropic cylindrical shells using multiple perturbation load approach – Simulation and validation. (December 2018) - Jiao, Peng; Chen, Zhiping; Tang, Xiaoyu; Su, Wenqiang; Wu, Jihang
Abstract: Thin-walled cylindrical shells subjected to axial load are prone to buckling and very sensitive to the geometric imperfections. In order to determine a rational design load for axially loaded cylindrical shells, different analytical and numerical design methods have been developed. As an extension of single perturbation load approach (SPLA), multiple perturbation load approach (MPLA) is a promising method but has not been thoroughly studied. In this paper, the buckling tests of three steel cylindrical shell specimens are conducted. Combined with experimental and numerical results, the advantages and limitations of several commonly used design methods are discussed in detail, including NASA SP-8007, the measured imperfection approach, SPLA and MPLA. The results validate that SPLA is indeed risky to be adopted as a design method for isotropic metallic cylindrical shells. Meanwhile, it indicates that MPLA can not only improve the knock-down factor but also give a more safe design load than SPLA. The comprehensive numerical investigations are performed to study the effects of each perturbation load parameter on MPLA, including the number of perturbation loads, their relative position and magnitude. It is found that the symmetry of perturbation loads plays an important role in the global buckling load of cylindrical shell. Moreover, some guidance for the future application of MPLA is provided and the four perturbation load approach (4PLA) is proposed as an improved method for the preliminary design of isotropic metallic cylindrical shells. Highlights: The applicability of MPLA in the design of steel cylindrical shell is validated by buckling tests. Compared with SPLA, MPLA is a more rational and safe design method for isotropic metallic cylindrical shells. The symmetry of perturbation loads plays an important role in the global buckling load. 4PLA is proposed as an improved design method for metallic cylindrical shells.